2014
DOI: 10.1590/1678-775720130488
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled clinical trial of long-term chemo-mechanical caries removal using PapacarieTM gel

Abstract: ObjectivesCompare the effectiveness of PapacarieTM gel for the chemo-mechanical removal of carious lesions on primary teeth to conventional caries removal with a low-speed bur with regard to execution time, clinical aspects and radiographic findings. Material and MethodsA randomized controlled clinical trial with a split-mouth design was carried out. The sample was composed of 20 children aged four to seven years, in whom 40 deciduous teeth were randomly divided into two groups: chemo-mechanical caries removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
1
20
0
2
Order By: Relevance
“…Two [ 26 , 27 ] included studies followed a cross-over trial design, while eighteen [ 10 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] had a split-mouth design. One study [ 45 ] followed a two parallel-arms trial, five studies [ 46 , 47 , 48 , 49 , 50 ] provided one treatment per patient while five studies [ 15 , 51 , 52 , 53 , 54 ] had one or more treatment per patient.…”
Section: Resultsmentioning
confidence: 99%
“…Two [ 26 , 27 ] included studies followed a cross-over trial design, while eighteen [ 10 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] had a split-mouth design. One study [ 45 ] followed a two parallel-arms trial, five studies [ 46 , 47 , 48 , 49 , 50 ] provided one treatment per patient while five studies [ 15 , 51 , 52 , 53 , 54 ] had one or more treatment per patient.…”
Section: Resultsmentioning
confidence: 99%
“…The trials’ publication date was from 2009 to 2016. Among these trials, three articles reported the same experiment; therefore, they were combined as Motta 2013–2014. Different regimens of the Papacarie method were identified in the included articles.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, five trials discussed the change in bacteria in the caries lesion, and two trials were excluded in the meta‐analysis for a lack of mean and SD data. In addition, 10 trials assessed the outcomes of pain perception before and after different caries removal methods; nevertheless, the scales used in these trials differ considerably. Only three trials used the Wong‐Baker‐Face Pain Scale (WBF) to evaluate pain perception and were remained eligible.…”
Section: Resultsmentioning
confidence: 99%
“…This papain-based gel is basically composed of a proteolytic enzyme that interacts with the partially degraded collagen present in the necrotic carious tissue (7). Some studies have addressed the effects of chemo-mechanical caries removal agents, in terms of clinical efficacy, acceptability, levels of pain, and success in the long term (3,(10)(11)(12)(13)(14). The effects of Papacárie Duo® on macrophage behaviour is not known, and its effects in cytotoxicity, viability and differentiation of undifferentiated dental pulp cells is scarce.…”
Section: Introductionmentioning
confidence: 99%